Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class

Ex 7.6

Ex 7.6, 1

Ex 7.6, 2 Important

Ex 7.6, 3 You are here

Ex 7.6, 4

Ex 7.6, 5 Important

Ex 7.6, 6

Ex 7.6, 7 Important

Ex 7.6, 8

Ex 7.6, 9

Ex 7.6, 10 Important

Ex 7.6, 11

Ex 7.6, 12

Ex 7.6, 13 Important

Ex 7.6, 14 Important

Ex 7.6, 15

Ex 7.6, 16

Ex 7.6, 17

Ex 7.6, 18 Important

Ex 7.6, 19

Ex 7.6, 20 Important

Ex 7.6, 21

Ex 7.6, 22 Important

Ex 7.6, 23 (MCQ)

Ex 7.6, 24 (MCQ) Important

Last updated at May 29, 2023 by Teachoo

Ex 7.6, 3 Integrate the function 𝑥^2 𝑒𝑥 ∫1▒〖𝑥^2 𝑒^𝑥 𝑑𝑥〗 = 𝑥^2 ∫1▒〖𝑒𝑥 𝑑𝑥〗−∫1▒(𝑑(𝑥^2 )/𝑑𝑥 ∫1▒〖𝑒𝑥 𝑑𝑥〗) 𝑑𝑥 = 𝑥^2. 𝑒𝑥 −∫1▒〖2𝑥 . 𝑒𝑥〗 𝑑𝑥 = 𝑥^2. 𝑒𝑥 −2∫1▒〖𝒙 . 𝒆𝒙〗 𝒅𝒙 Now we know that ∫1▒〖𝑓(𝑥) 𝑔(𝑥) 〗 𝑑𝑥=𝑓(𝑥) ∫1▒𝑔(𝑥) 𝑑𝑥−∫1▒(𝑓′(𝑥)∫1▒𝑔(𝑥) 𝑑𝑥) 𝑑𝑥 Putting f(x) = x2 and g(x) = ex …(1) Solving I1 ∫1▒〖𝑥 𝑒^𝑥 𝑑𝑥〗 = 𝑥∫1▒𝑒𝑥 𝑑𝑥−∫1▒(𝑑𝑥/𝑑𝑥 ∫1▒𝑒^𝑥 𝑑𝑥) 𝑑𝑥 = 𝑥𝑒𝑥 −∫1▒𝑒𝑥 𝑑𝑥 = 𝑥𝑒𝑥 −𝑒𝑥 Now we know that ∫1▒〖𝑓(𝑥) 𝑔(𝑥) 〗 𝑑𝑥=𝑓(𝑥) ∫1▒𝑔(𝑥) 𝑑𝑥−∫1▒(𝑓′(𝑥)∫1▒𝑔(𝑥) 𝑑𝑥) 𝑑𝑥 Putting f(x) = x and g(x) = ex Putting value of I1 in our equation ∴ ∫1▒〖𝑥^2 𝑒𝑥" " 〗 𝑑𝑥" = " 𝑥^2. 𝑒𝑥 −2∫1▒〖𝒙 . 𝒆𝒙〗 𝒅𝒙 =𝑥^2. 𝑒𝑥 −2(𝒙𝒆𝒙−𝒆^𝒙 )+𝐶 =𝑥^2. 𝑒𝑥 −2𝑥𝑒𝑥+〖2𝑒〗^𝑥+𝐶 =𝒆𝒙 (𝒙^𝟐−𝟐𝒙+𝟐)+𝑪